Prevalência do ectrópio palpebral e características dos portadores na população da região Centro-Oeste do Estado de São Paulo - do Silva, Cristiane Prado [UNESP]; Schellini, Silvana Artioli [UNESP]; Padovani, Carlos Roberto [UNESP]; Narikawa, Silvia [UNESP] (My University, 2009)
Purpose: To present the characteristics of individuals and the prevalence of ectropium eyelid in a random sample of the state of São Paulo, Brazil. Methods: Data were collected during the Project on Prevention of Blindness, Faculty of Medicine of Botucatu - UNESP, a systematic random household sample was obtained. We evaluated 10,432 individuals, residents in 11 cities of the health regional located in the Central-Western region of the state of São Paulo. The results were submitted to statistical analysis to evaluate descriptive variables and the prevalence of ectropium eyelid. Results: Seventy-one ectropium eyelid patients were detected, with an estimated prevalence of 0.68%. The prevalence was not similar in all the studied municipalities. Most people with ectropium eyelid presented age over 70 years and were male. Cataract was concurrently present in 28.0% of them. Conclusion: The prevalence of ectropium population in the Central-Western region of São Paulo state is 0.68%. The ectropium eyelid affect mainly male, over 70 years relating sun light exposition and with normal visual acuity.
Eyelid ectropium prevalence and carriers characteristics in a population from the Center-Western region of São Paulo State
Keywords: Brazil/epidemiology; Ectropion/epidemiology; Eye diseases/epidemiology; Prevalence; Visual acuity